A staged approach with initial tumor thrombectomy followed by hepatectomy for icteric-type hepatocellular carcinoma: A case report. (2019) - Yazawa, Takehisa; Ohta, Takehiro; Ariizumi, Shun-ichi; Takahashi, Yutaka; Higuchi, Ryota; Yamamoto, Masakazu
Highlights: Obstructive jaundice due to tumor thrombus in the common bile duct with HCC is classified as icteric-type HCC. Biliary drainage for patients with icteric-type HCC is sometimes difficult. A staged approach with initial tumor thrombectomy followed by hepatectomy should be considered as one of the options for icteric-type HCC. Abstract: Introduction: Biliary drainage for patients with icteric-type hepatocellular carcinoma (HCC) is sometimes difficult, because the drainage tube makes contact with the tumor thrombus (TT) and effective drainage cannot be achieved due to hemobilia. Presentation of case: We performed endoscopic naso-biliary drainage for an icteric-type HCC patient; however, the serum bilirubin level was not decreased due to bleeding from the TT. Therefore, we performed tumor thrombectomy in the bile duct and transection of the right hepatic bile duct prior to right hepatectomy. After the first operation, the bilirubin level was decreased, and liver function was recovered so that the patient could undergo right hepatectomy 4 months after the first operation. The postoperative course was uneventful after the second operation and the patient was discharged from the hospital on the 30th postoperative day. The patient is well without recurrence 10 years after surgery. Conclusion: Biliary drainage is one of the key points for successful treatment of icteric-type HCC patients. A staged approach with initial tumor thrombectomy followed by hepatectomy should be considered as one of the options for icteric-type HCC.